2020
DOI: 10.24093/awej/vol11no4.11
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Obstacles of Using the Internet in Language Teaching from Instructors’ Perspective; the case of the department of English at Imam Mohammad Ibn Saud Islamic University

Abstract: This study investigated the instructors’ perceived obstacles and needs in using the Internet for teaching English. Eighty-one instructors in the Department of English at Imam Mohammad ibn Saud Islamic University (IMSIU) participated in the study. This study provides data related to the teachers' perceptions concerning Internet use, areas and barriers in language teaching. The study aimed to answer two research questions. Namely, what are the perceived obstacles to implementing Internet-based English as a forei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Research studies conducted during the post-COVID era present contradictory findings compared to the pre-COVID context. Accordingly, the levels of competence in technology were not sufficient for implementing education at a distance, and it was found that teachers had difficulty in moving and establishing themselves on digital platforms due to a lack of prior exposure [30,31,36,37,39,[58][59][60][61]. Various difficulties in adapting to technology during the early stages of the transition were observed.…”
Section: Teacher's Competency and Confidence In Using Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Research studies conducted during the post-COVID era present contradictory findings compared to the pre-COVID context. Accordingly, the levels of competence in technology were not sufficient for implementing education at a distance, and it was found that teachers had difficulty in moving and establishing themselves on digital platforms due to a lack of prior exposure [30,31,36,37,39,[58][59][60][61]. Various difficulties in adapting to technology during the early stages of the transition were observed.…”
Section: Teacher's Competency and Confidence In Using Technologymentioning
confidence: 99%
“…Further, it is claimed that digital literacy is significantly influenced by the teacher's attitude over other contextual factors such as education level, gender, and experience [95]. Teachers, in general, possess a positive attitude towards technologyenhanced teaching [22,36,38,48,50,53,62]. In contrast, the findings of Jwaifell et al [34] and Makina and Madiope [49], before the pandemic, justify that teachers may not necessarily have a positive attitude towards technology due to teachers' robust connection to conventional teaching strategies.…”
Section: Teacher's Attitudes and Motivation Towards Technology Enhanc...mentioning
confidence: 99%
See 3 more Smart Citations